1982
DOI: 10.1128/aac.22.6.1051
|View full text |Cite|
|
Sign up to set email alerts
|

Lysis of Trypanosoma cruzi by Pseudomonas fluorescens

Abstract: Trypomastigotes of Trypanosoma cruzi isolated from the blood of infected mice were lysed within 24 h by an extracellular substance produced by Pseudomonas fluorescens. Isolation of the anti-trypanosomal factor (ATF) was accomplished by growth of the organisms in a defined medium, extracellular secretion by the sedimented cells, sterilization by filtration, lyophilization, dialysis, and gel filtration. Chromatographic separation with Sephadex G-25 and G-200 disclosed the occurrence of three active fractions. AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…For the beneficial Pseudomonas species, a range of functions and activities have been reported (Raaijmakers et al ., 2006). For example, viscosin was shown to have antiviral activity (Groupe et al ., 1951) and to cause lysis of trypomastigotes of the human pathogen Trypanosoma cruzi , the causal agent of Chagas' disease (Mercado and Colon‐Whitt, 1982). For strain P. fluorescens SBW25, we focused on the role of CLP synthesis in surface motility, biofilm formation and activity against zoospores of P. infestans , the causal agent of late blight of tomato and potato.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the beneficial Pseudomonas species, a range of functions and activities have been reported (Raaijmakers et al ., 2006). For example, viscosin was shown to have antiviral activity (Groupe et al ., 1951) and to cause lysis of trypomastigotes of the human pathogen Trypanosoma cruzi , the causal agent of Chagas' disease (Mercado and Colon‐Whitt, 1982). For strain P. fluorescens SBW25, we focused on the role of CLP synthesis in surface motility, biofilm formation and activity against zoospores of P. infestans , the causal agent of late blight of tomato and potato.…”
Section: Resultsmentioning
confidence: 99%
“…2000). Also for the human pathogen T. cruzi , similar microscopic observations have been made (Mercado and Colon‐Whitt, 1982). In their study, the viscosin‐producing P. fluorescens isolate approached a single flagellate of T. cruzi at the posterior end, the site of the flagellar origin, resulting in immobilization.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Pseudomonas putida decreases Plasmodium falciparum levels in Anopheles gambiae mosquitoes [ 23 ], and Pseudomonas fluorescens causes T . cruzi lysis in vitro [ 55 ]. It is possible that some of the Pseudomonas species present in all T .…”
Section: Discussionmentioning
confidence: 99%
“…In sandflies ( Phlebotomus papatasi ), microbial infections significantly reduced the rates of infection with Leishmania major (Schlein et al, 1985). In addition, strains of Pseudomonas fluorescens (Mercado and Colon-Whitt, 1982), as well as of S. marcescens (which was isolated from Rhodnius prolixus ) (Azambuja et al, 2004) have been reported to be able to lyse Trypanosoma cruzi in vitro . All these examples show potential implication of bacteria isolated from insects in their vector competence.…”
Section: Involvement Of Midgut Bacteria In the Insect Vector Competenmentioning
confidence: 99%
“…(Thomson et al, 2000); hemagglutinins (Gilboa-Garber, 1972) and siderophore by P. aeruginosa (Schalk et al, 2002). An antitrypanosomal factor has been shown to be produced by P. fluorescens (Mercado and Colon-Whitt, 1982). Pigments such as prodigiosin are produced by the Gram-negative bacteria such as Serratia spp.…”
Section: Mechanisms Potentially Involved In the Modulation Of Parasitmentioning
confidence: 99%